A slow fire burning - Hawkins, Paula (Doubleday, 2021)
Laura has spent most of her life being judged. She's seen as hot-tempered, troubled, a loner. Some even call her dangerous. Miriam knows that just because Laura is witnessed leaving the scene of a horrific murder with blood on her clothes, that doesn't mean she's a killer. Innocent or guilty, everyone is damaged. Some are damaged enough to kill.